Analyzing the Mechanical, Durability, and Microstructural Impact of Partial Cement Replacement with Pumice Powder and Bamboo Leaf Ash in Concrete - Haris Hassen Adem; Fikreyesus Demeke Cherkos (Advances in Civil Engineering)
This study explores the physiomechanical and durability properties of C-25 concrete by partially replacing cement with blends of pumice powder (PP) and bamboo leaf ash (BLA). The combined amount of major oxides SiO2, Al2O3, and Fe2O3 in PP is 84.59%, while in BLA, it is 74.4%, classifying PP and BLA as class N and F pozzolans. Subsequently, the study examines the impact of different cement replacement percentages, emphasizing 5%, 10%, 15%, and 20% on C-25 with varying mixes of concrete: Mix-1 (100, 0, and 0), Mix-2 (90, 5, and 5), Mix-3 (85, 10, and 5), Mix-4 (85, 5, and 10), and Mix-5 (80, 10, and 10) which correspond to the proportions of OPC, VPP, and BLA used in each mix respectively and by using 1 : 2.34 : 2.68 (cement : sand : aggregate) with the water/cement ratio (w/c) of 0.491. The study’s findings indicate that as the proportion of PP and BLA increases in concrete, the workability of the mixture decreases. Moreover, on the 28th day, Mix-2 with (35.84 MPa) and Mix-3 with (33.55 MPa) met the desired mean compressive strength (33.5 MPa) required for C-25 concrete per the ACI standards. Additionally, the flexural strength of concrete produced with partial replacement of Mix-2 with a flexural strength of 3.86 MPa fulfills the minimum strength requirement of 3.5 MPa specified by the C-25 ACI standards. The PP and BLA blended concrete had lower water absorption than the control mix in Mix-2. It also improved resistance to sulfuric acid attack, and Mix-3 had the least strength reduction of 9.59%. In contrast, the control mix has a 33.34% strength reduction.